The immune system response to the SARS-CoV-2 virus: December 2020 update - Klenerman, Paul (Henry Stewart Talks, 2020)
Update on the immune response to SARS-CoV-2, Current knowledge on the stability of the immune response, The role of interferon alpha in the response, The new virus strain in the UK (VUI – 202012/01), Research looking into the long-term health issues arising from COVID-19